Boyle on Atheism. - MacIntosh, J. J. (Toronto studies in philosophy., 2014)
With Boyle on Atheism, J.J. MacIntosh has culled the Boyle manuscripts held at the Royal Society Library in London and transcribed the portions that relate to atheism, arranging them in the order Boyle appears to have intended.